Epidemiology of human leptospirosis in Malaysia, 2004–2012 - Benacer, Douadi; Thong, Kwai Lin; Ng, Choung Min; Verasahib, Khebir; Galloway, Renee Lynn; Hartskeerl, Rudy A.; Souris, Marc; Mohd Zain, Siti Nursheena (Elsevier, 2016)
Leptospirosis is an emerging disease, especially in countries with a tropical climate such as Malaysia. A dramatic increase in the number of cases has been reported over the last decade; however, information on the epidemiological trends of this disease is lacking. The objective of this study is to provide an epidemiological description of human leptospirosis cases over a 9-year period (2004–2012) and disease relationship with meteorological, geographical, and demographical information.